Effectiveness and safety of thiotepa as conditioning treatment prior to stem cell transplant in patients with central nervous system lymphoma. Issue 12 (December 2014) - Kokolo, Madzouka B.; Fergusson, Dean; O'Neill, Joseph; Tay, Jason; Tinmouth, Alan T.; Stewart, Douglas; Bredeson, Chris
Abstract Background. Thiothepa is a cytostatic agent used in managing solid malignancies, and also as conditioning treatment before hematopoietic stem cell transplantation [HSCT]. This systematic review summarizes evidence on its effectiveness and safety, in patients with central nervous system [CNS] lymphoma. Methods. We searched 3 databases for clinical studies. When feasible, we performed meta-analyses. Results. We identified 13 eligible studies, none of which with a priori controls. So data synthesis focused on the 226 patients who received thiotepa. Based on pooled estimates, 75.9% of thiotepa-treated patients achieved a complete remission (95% confidence interval [CI] = 67.5–82.8), and 61.7% had a progression-free survival for up to 125 months post-treatment (95% CI = 49.4–72.7). However, 25.5% relapsed, 24.6% experienced infection, and 13.2% experienced neurotoxicity. Discussion. Thiotepa-based conditioning followed by HSCT may be effective in most CNS lymphoma patients, with a manageable toxicity profile. But adequately powered randomized trials are needed to better evaluate and isolate the effects of thiotepa.